Determinants of LMS Continuance Intention: An Extended UTAUT Approach - Ngakan Nyoman Kutha Krisnawijaya; Ni Made Dhian Rani Yulianti; Ni Putu Dhanan Kumaradewi M; Anak Agung Adi Wiryya Putra (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the factors influencing user satisfaction and continuance intention of Learning Management Systems (LMS) among international students in a mandatory academic ecosystem. This study has significant significance in bridging the theoretical gap between the cognitive adoption model (UTAUT) and the affective post-adoption evaluation (ECM) in a tech-savvy cross-cultural user segment. Using a causal-associative quantitative design, data were collected through a structured online questionnaire from 71 International Undergraduate Program (IUP) student respondents selected through a purposive sampling method. Data analysis was conducted using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS software version 4.0. The results of the path analysis showed that effort expectancy and social influence had a positive and significant effect on satisfaction, while performance expectancy and facilitating conditions did not show a significant effect. Furthermore, satisfaction was proven to exclusively mediate the effect of effort expectancy on continuance intention of LMS. The implications of this research confirm that in institutionally mandated systems, user motivation shifts to academic compliance. Therefore, higher education institutions are advised to prioritize eliminating everyday technical barriers through intuitive interface design to foster genuine international student satisfaction.